Urban Forest Conservation through the Lens of Ecological Exegesis: An Analysis of Surah Qaf: 9-11 - Wahyudin, Muhammad; Rifai, Abdusshomad (Universitas Muhammadiyah Surakarta, 2026)
The escalating urban environmental crises, such as flooding and air pollution, demand beyond mere technical interventions; they require robust ethical-theological frameworks. While existing Islamic eco-theology predominantly discusses general environmental ethics, there is a distinct research gap in operationalizing specific Qur'anic verses into practical urban spatial policies. Therefore, this study aims to bridge classical theological interpretations of Surah Qaf: 9-11 with the modern regulatory concept of Green Open Space (RTH). Employing a qualitative library research design, this study utilizes the thematic exegesis (maudhu'i) approach formulated by Al-Farmawi. The primary data, sourced from authoritative classical commentaries (Ibn Kathīr, al-Rāzī, and Ibn 'Ashūr), were systematically analyzed using Abdullah Saeed's textual-contextual framework to synthesize classical theology with contemporary urban hydrology and microclimate science. The results indicate three key findings: (1) mā'an mubārakan (blessed water) aligns with sustainable urban hydrology and water security principles; (2) jannāt (gardens) serves as the theological equivalent of urban forests, functioning as vital ecosystem buffers and microclimate regulators; and (3) rizqan lil-'ibād (sustenance for servants) frames conservation not merely as a biological need, but as a socio-economic and spiritual mandate (amānah) for human stewardship (khalīfah). The novelty of this research lies in its specific formulation of